Neuropeptide FF receptors as novel targets for limbic seizure attenuation. (August 2015) - Portelli, Jeanelle; Meurs, Alfred; Bihel, Frederic; Hammoud, Hassan; Schmitt, Martine; De Kock, Joery; Utard, Valerie; Humbert, Jean-Paul; Bertin, Isabelle; Buffel, Ine; Coppens, Jessica; Tourwe, Dirk; et al.
Abstract: Neuropeptide Y (NPY) is a well established anticonvulsant and first-in-class antiepileptic neuropeptide. In this study, the controversial role of NPY1 receptors in epilepsy was reassessed by testing two highly selective NPY1 receptor ligands and a mixed NPY1 /NPFF receptor antagonist BIBP3226 in a rat model for limbic seizures. While BIBP3226 significantly attenuated the pilocarpine-induced seizures, neither of the highly selective NPY1 receptor ligands altered the seizure severity. Administration of the NPFF1/NPFF2 receptor antagonist RF9 also significantly attenuated limbic seizure activity. To further prove the involvement of NPFF receptors in these seizure-modulating effects, low and high affinity antagonists for the NPFF receptors were tested. We observed that the low affinity ligand failed to exhibit anticonvulsant properties while the two high affinity ligands significantly attenuated the seizures. Continuous NPFF1 receptor agonist administration also inhibited limbic seizures whereas bolus administration of the NPFF1 receptor agonist was without effect. This suggests that continuous agonist perfusion could result in NPFF1 receptor desensitization and mimic NPFF1 receptor antagonist administration. Our data unveil for the first time the involvement of the NPFF system in the management of limbic seizures. Highlights: Specific NPY1 receptor ligands do not affect pilocarpine-induced seizures. The mixed NPY1/NPFF ligand BIBP3226 attenuates evoked seizures. NPFF receptor antagonists significantly decrease the evoked limbic seizures. This study shows for the first time the involvement of the NPFF system in epilepsy.